(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2023)
With the increasing complexity of business transactions, and increasing business risk, the role of competitive management accounting is becoming increasingly important, especially in making strategic business decisions. As a part of strategic management accounting, competitive management accounting positions the company to a place which has the best view of the existing and potential competitor activity, by creating a strong information base on competition, all to create added value and improve the company operations. This paper aims to highlight the importance of competitive management accounting in strategic decision-making, and based on case studies in the world and empirical research conducted in Iraq, to highlight the importance of competitive management accounting in the world and to answer the question of whether the companies in Jordon use the information from competitive management accounting in the process of decision-making?